ANALISIS KEY SUCCESS FACTORS SEBAGAI ALAT MEMPERTAHANKAN KEUNGGULAN BERSAING - dewi, Amalia nur diana; Rahayu, Yuliastuti (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
The purpose of this research is to identify and to conduct analysis to achieve key success factors as the standard of performance to reach and to maintain the competitive advantage on PT Indimex Selo Anti Geni.This research applies qualitative descriptive method which is done by collecting data, conducting interview to all related employees in PT Indimex Selo Anti Geni, based on explanations and descriptions which is done by making comparison among the data that have been obtained to the existing basic theories then the analysis is conducted.The emerging problem is that there are business competitors in the refractory field. The competitors are getting more aggressive in competing to get into the market. So, PT Indimex Selo Anti Geni should make a strategy to maintain their eminence in the existing competition.Based on the result of the analysis and the discussion which has been carried out on PT Indimex Selo Anti Geni, it can be concluded that the company has strengths and opportunities to expand. It is recommended that the company should keep on improving their human resources. The company should achieve the key success factors in maintaining the competitive advantage so it is threatened by the emergence of competitors.Keywords: Key Success Factors, Performance, SWOT, Competitive Advantage